Goth YouTubers and the informal mentoring of young goths: peer support and solidarity in the Greek goth scene. (13th September 2020) - Karampampas, Panas
ABSTRACT: This ethnographic article is the first contribution to the topic of the informal mentoring of YouTube vloggers (video bloggers) also known as YouTubers and focuses on the practices of young Greek goth YouTubers and their viewers. Goth YouTubers create videos as a response to problems that they personally face, which include challenges such as bullying, and dealing with negative descriptions of themselves. YouTubers take advantage of available features of multiple social media platforms which they utilise in combination with YouTube and performative techniques to create a sense of un-mediation with their viewers. The result of this is that the viewers develop a sense of intimacy with the You Tubers, and see similarities in their lives, and consequently feel able to ask the advice of the YouTuber. Goth YouTubers personally reply to their viewers with personal messages or videos. These interactions take the form of an informal mentoring which contributes to the building of solidarity within the goth scene. Thus, the article concludes that informal mentoring becomes central to the integration of new goths into the scene, into learning about the scene itself, and furthermore, as an aid to coping with problems that they face.